IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING PADA MASA PANDEMI COVID 19 DI PAUD ISTIQOMAH SAMBAS - -, Novi Indrawati (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This study aims to provide an overview of the application of distance learning with the blended learning method in Istiqomah Sambas PAUD. The research method used is a qualitative method. Interviews and documentation are the main techniques for collecting data in research. The collected data were analyzed using steps, namely data reduction, data presentation, drawing conclusions and verification. The result of the research is Blended learning which is implemented in PAUD Istiqomah Sambas, namely the full blended learning model. With a time allocation of 66.67% for online learning and 33.33% for offline learning. Online learning is carried out through Google Classroom and zoom meetings while offline learning is carried out individually through a home visit. Learning assessment is carried out through observation of photo documents or videos of student activities and observation of the process of playing activities by parents. The results of the learning implementation are as follows: The activeness of students in sending learning assignments through Google Classroom is 76.56%, the attendance of students in virtual learning through zoom meetings is 86.99%, while in home visit learning is 94.2%. The achievement of students' development in the first semester of the 2020/2021 school year was 63.69%.Blended learning, PAUD, Covid 19